Isolasi, Identifikasi Struktur Molekul Flavonoid dari Daun Belimbing Wuluh (Averrhoa bilimbi L.) dan Uji Kuantitatif Aktivitas Antijamur terhadap Candida albicans - I Kadek pater Suteja; Egi Azikin Maulana; Dewa Gd. Agung Yudha Pratama (Pure Chemistry Research, 2025)
This study aimed to isolate and elucidate the molecular structure of flavonoid compounds from bilimbi (Averrhoa bilimbi L.) leaves and to evaluate their antifungal activity against Candida albicans. Extraction was performed using maceration with 96% ethanol, followed by sequential fractionation with n-hexane, ethyl acetate, and methanol. Purification of the target compound was achieved through column chromatography and preparative thin-layer chromatography. Structural identification using UV–Vis, FTIR, and 1H/13C NMR spectroscopy confirmed that the isolated compound belongs to the flavonol class, characterized by aromatic hydroxyl groups and a conjugated flavonoid system. Although the yield of the purified compound was relatively low, its high purity enabled accurate structural characterization. Antifungal activity was quantitatively evaluated using the broth microdilution method. The isolated flavonoid exhibited significant antifungal activity against C. albicans, with a minimum inhibitory concentration (MIC) of 125 µg/mL and a minimum fungicidal concentration (MFC) of 250 µg/mL. The antifungal activity of the pure compound was higher than that of the semi-polar ethyl acetate fraction, indicating that the biological activity was predominantly attributed to the isolated flavonoid. The proposed antifungal mechanism involves disruption of fungal cell membrane integrity and inhibition of cell wall synthesis. Overall, this study demonstrates the potential of flavonoids from A. bilimbi leaves as natural antifungal agents, warranting further investigation for pharmaceutical development.